PRODUKTIVITAS KERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH PROVINSI SUMATERA BARAT - YANIK SULISTIO NINGRUM (Jurnal Bahana Manajemen Pendidikan, 2018)
This reserch is motivated from observation of the author in Badan Kepegawaian Daerah Provinsi Sumatera Barat of the show is still not in accordance with proper. The reserch question posed is how to worck productivity employees at Badan Kepegawaian Daerah Provinsi Sumatera Barat views of employee effectiveness and employee efficiency? This is a deskriptive study with a population of 67 poeople. Samples werw taken by Propotional Statified randoam sampling. Technique with a sample of 60 people. Data collection tool was a questionnaire drawn up in the from of Likert Scale. The results showed productivity of employees working in Badan Kepegawaian Daerah Provinsi Sumatera Barat. Has been good with an average score of 3,6 in both cetegories.